The Psychological Status of General Population in Hubei Province During the COVID-19 Outbreak: A Cross-Sectional Survey Study - Chen, Guanmao; Gong, Jiaying; Qi, Zhangzhang; Zhong, Shuming; Su, Ting; Wang, Jurong; Fu, Siying; Huang, Li; Wang, Ying (Frontiers in Public Health, 2021)
Introduction: The current outbreak of the novel coronavirus disease 2019 (COVID-19, previously 2019- nCoV), originating from Wuhan (Hubei province, China), has rapidly spread across China and several other countries. During the outbreak of COVID-19, the mental health of the general population in Hubei Province (China) may be affected. Methods: A cross-sectional online survey was used to evaluate the symptoms of distress, depression and anxiety which were assessed by the Chinese version of the Impact of Event Scale-Revised (IES-R), Patient Health Questionnaire-9 (PHQ-9), and 7-item Generalized Anxiety Disorder Scale (GAD-7), respectively. Coping style was assessed by Simplified Coping Style Questionnaire (SCSQ). Multivariate logistic regression analysis was carried out to detect factors associated with mental health outcomes. Results: Among 9225 participants, 44.5% rated distress symptoms, and 17.9% and 12.7% suffered from moderate or above level of depression and anxiety symptoms, respectively. Individuals who were geographically located in Wuhan and familiar with someone to have COVID-19 had higher levels of distress, depression, and anxiety symptoms, as well as higher score of passive coping style (P < 0.05). Multivariate logistic regression analysis showed that individuals who were geographically located in Wuhan (OR = 1.25, P < 0.001) were found to be associated with severe symptoms of distress. Besides, individuals who were familiar with someone to have COVID-19 (OR = 2.33, P < 0.001; OR = 1.90, P < 0.001; OR = 2.06, P < 0.001) and had higher score of passive coping style (OR = 1.16, P < 0.001; OR = 1.17, P < 0.001; OR = 1.17, P < 0.001) were noted to be associated with severe symptoms of distress, depression, and anxiety. Moreover, higher score of active coping style (OR = 0.96, P < 0.001; OR = 0.94, P < 0.001; OR = 0.95, P < 0.001) was associated with a lower risk of symptoms of distress, depression, and anxiety. Conclusions: The findings may lead to better understand the psychological status of general public, and obviate the public mental health crisis during the COVID-19 outbreak.